American History: A Survey, Volume 2, Since 1865 - Brinkley Alan (American : Mc Graw-Hill, 2007)
Highly respected for its impeccable scholarship and elegant writing style, Alan Brinkley's American History provides students and instructors with a reliable, comprehensive account of the American past in which no single approach or theme predominates. From its first edition, this text has included a scrupulous account of American political and diplomatic history. Today, the book explores areas of history such as social, cultural, urban, racial and ethnic history, the history of the West and South, environmental history, the history of women and gender, and American history in a global context. The twelfth edition of this text includes the McGraw-Hill's hit Primary Source Investigator (PSI) cd-rom, with hundreds of sources and a program that walks students through how to write a paper using those sources as evidence.
Keywords: History-American